Notes on the “Stele of the Punishments” from Epidaurus (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2025)
This essay examines several legal aspects in the recently published “Stele of the Punishments” fromEpidaurus. The essay shows that the search of the house of Pasiteles in Hermione for stolen goodsby officials from Epidaurus was in no way illegal. In the account of the search the text mentions therole of a slave to establish the liability of Lykiskos. Pasiteles was summoned before the ThreeHundred at Epidaurus, questioned about his actions, and asked to name sureties, to swear an oath ofdenial, and to pay court fees. After he did not show up at his trial, the Three Hundred found himguilty of theft, condemned him to a fine of double the amount stolen, and voted to confiscate hisproperty. Some time later, Lykiskos was condemned to pay a fine either for his role in this theft orfor another offense. The legal procedure followed in the cases reveals similarities and differencesfrom legal procedure at Athens. Finally, the stele aimed to warn those working in the sanctuaryagainst embezzling valuable items and also demonstrated to Greek visitors to the shrine ofAsclepius that the people of Epidaurus upheld the basic tenets of the rule of law.Questo saggio esamina diversi aspetti giuridici della recentemente pubblicata “Stele dellepunizioni” di Epidauro. Il saggio dimostra che la perquisizione della casa di Pasiteles a Ermione,alla ricerca di beni rubati, da parte dei funzionari di Epidauro non era affatto illegale. Nel resocontodella perquisizione, il testo menziona il ruolo di uno schiavo nel determinare la responsabilit. diLykiskos. Pasiteles fu convocato davanti ai Trecento a Epidauro, interrogato sulle sue azioni einvitato a nominare dei garanti, a prestare giuramento di negazione e a pagare le spese processuali.Dopo che non si present. al processo, i Trecento lo dichiararono colpevole di furto, locondannarono a una multa pari al doppio dell'importo rubato e votarono di confiscare i suoi beni.Qualche tempo dopo, Lykiskos fu condannato a pagare una multa per il suo ruolo in questo furto oper un altro reato. La procedura legale seguita nei casi in questione rivela somiglianze e differenzerispetto alla procedura legale in uso ad Atene. Infine, la stele aveva lo scopo di mettere in guardiacoloro che lavoravano nel santuario dal sottrarre oggetti di valore e dimostrava anche ai visitatorigreci del santuario di Asclepio che il popolo di Epidauro sosteneva i principi fondamentali delloStato di diritto.
Keywords: Epidaurus; house-searches in Greek Law; legal procedure (Greece); oaths in litigation; theft; rule of law as source of legitimacy